Population-Based Surveillance of Invasive Group A Streptococcal Disease in British Columbia: 1996-1998 - Gordean L Bjornson; David W Scheifele; Alison Bell; Arlene King (Canadian Journal of Infectious Diseases)
OBJECTIVE: To identify and describe all cases of invasive group A streptococcal (GAS) infection occurring in British Columbia during a two-year period.